(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article provides information on research conducted by the staff of the Botanical garden regarding greening of the tideline of lake Yssyk-Kul and a list of their works published from 1959 to 1996